Analysis of Teaching Materials and Learning Methods for the Professionalism and Leadership Course in the Implementation of Religious Moderation in Islamic Early Chilhood Education Study Program, State Islamic University Sunan Kalijaga Yogyakarta - Pangestuti, Puji; Nadlifah, Nadlifah; Rokhimawan, M Agung; Hanifatunnisa, Hanifatunnisa; Sihono, Sihono; Lesvinanda, Adhelia Shelyn (SAINTIS Publishing, 2025)
This study aims to determine how religious moderation is implemented in the teaching materials and learning methods of the